(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2023)
In this article, we explore community dreamwork as a form of intercultural peace learning pedagogy and community building and will connect this to themes of epistemic justice, decolonial praxis, and the importance of the learning that occurs in the in-between spaces. We explore questions of formal and informal learning spaces, our assumptions about where learning takes place, and the transformative potential of spontaneous, organic, emergent learning spaces that happen in the cracks of formal structures. We also explore our experience of simultaneous translation (Spanish-English) as a pedagogy of intercultural peacelearning that promotes epistemic justice and slowing down. We further critically examine the reliance of Freirean pedagogy within the field of peace education, particularly for its emphasis on rationality, as we believe it is necessary to reach beyond critical pedagogy through emotional, embodied, and other ways of knowing and being to achieve intercultural peace learning and sentipensante pedagogy. Building on Cremin, Echavarria, & Kester’s (2018) call for transrational pedagogy in peacebuilding education, we offer our experience of community dreamwork as an example of a transrational pedagogy that allows access to embodied, emotional, and spiritual ways of knowing.